Hematological parameters in champion of Brazilian jiu‐jitsu paradesport: Case study - Jaqueline S. S. Lopes; Aníbal M. deMagalhães Neto; Aline C. deAlmeida; Paulo R. L. Alves; Elcirley L. Silva; Márcio V. deAbreu Verli; Claudia M. B. Andrade (Physiological Reports, 2020)
Abstract The behavior of biochemical and immunological parameters investigated in the field conditions in athletes is important to influence in the management of recovery and disease prevention as well as, to support the training program, as well as to improve the physical conditioning associated with health and performance. However, for amputee athletes, Brazilian jiu‐jitsu paradesport practitioners, there are no published data to date. Thus, the objective of this case study was to quantify the magnitude of biochemical, hematological, and urinary alterations after a simulated fight session in elite athlete with world titles. Outcomes were obtained through blood analysis of samples collected at four different moments (M1‐fasting; M2—1.5 hr after caloric intake; M3—Immediately after the simulated fight; M4—24 hr after the simulated fight). Responses triggered by the simulated fight between baseline and after 24 hr were found to increase in monocyte (100%), neutrophil (20%), and insulin (57%) concentrations, while reductions were observed in eosinophils (−50%), lymphocytes (−26.6%), platelets (−22%), cortisol (−50%), and creatine phosphokinase (−45.2%). After 24 hr lactate values returned to baseline levels. The different changes in biochemical and hematological parameters observed constitute responses to acute physical exercise and were according to the level of the high performance athlete. From these data it will be possible to evaluate the periodization, training load, and recovery techniques according to the individual response verified. In addition, these data may be used for comparison purposes within this specific sport, whose literature is still limited.